Persepsi Mahasiswa dan Dosen Penasehat Akademik Tentang Tugas Penasehat Akademik di Jurusan Teknik Sipil Universitas Negeri Jakarta - Vian Rahmawati (Jurnal Pensil : Pendidikan Teknik Sipil, 2014)
The objectives of this study to determine the perception of students and faculty Academic Advisor on Academic Advisory assignments in the Department of Civil Engineering, State University of Jakarta. The study lasted for three months from September to November 2013.Place of research conducted at the Department of Civil Engineering, State University of Jakarta. The population in this study is the student of 2009-2012 amounted to 56 people and lecturer Academic Advisory force from 2009 to 2012 amounted to 14 people so that the total respondents numbered 70 people. The method used in this study is a survey method. The trial questionnaire of 60 statements. The test is done to 10 respondents. After the test phase the results obtained valid instruments as much as 50 point statement.Data analysis technique is done by searching percentage. The results show that: (a) Students have a negative perception about the task of the Advisory Academic faculty as mentors to students at 48,49% and the perception of the Academic Advisory lecturer on Academic Advisory duties as supervisor of students showed a positive perception of 59.58%. (B) Students have positive perceptions about the task of the Academic Advisory lecturer as student advisors at 53.67% and the perception of the faculty Academic Advisory Academic Advisory duties as student advisors showed a positive perception of 54.63%. (C) There is still a shortage of the Academic Advisory task that is in terms of guidance to the student schedule and record and monitor the progress of students study. Therefore there is need for improvement in this regard.